Clipper circuit of pulse modulator used for Klystron-5045 power supply - Akimov, A.V.; Kazarezov, I.V. (Вопросы атомной науки и техники, 2001)
While the operation of modulator to the pulsed transformer of klystron-5045, current through the primary winding of the pulse transformer (PT) continues to flow even upon the end of the klystron voltage operating pulse. This is determined by an energy stored in magnetizing inductance. The prolongation of magnetizing current passing process simultaneously with the premature choking of thyratron can cause high voltage of inverse polarity at the klystron, which cause the destruction of the cathode. We have considered the possibility of shortening time of magnetizing current passage for the charge of reasonable choice of clipper circuit parameters. The behavior of clipper circuit was studied in modulators used for the VEPP-5 (BINP, Russia) preinjector klystron power supply. The optimum operation run of the circuit was selected and its design features are described.